Pengaruh Citra Merek, Harga, Dan Kualitas Terhadap Keputusan Pemembelian Laptop Merek Axioo Di Kota Jambi - H Maulana Yusuf; Lidya Anggraeni; M Amrul Hadawi (JOURNAL SAINS STUDENT RESEARCH, 2023)
In deciding to buy a product, consumers make several considerations until they come to a decision to buy the product. Other factors that are taken into consideration are product quality, brand image of a product, and price. The importance of maintaining quality and brand image for a product will affect the level of consumer confidence. In addition, the prices offered by various products are an important factor in purchasing decisions. This study aims to determine the effect of brand image, price, and product quality on consumer decisions to buy Axioo brand laptops. This type of research is descriptive quantitative. Data obtained from distributing questionnaires, observation, and documentation. The method used to analyze the data is multiple regression analysis. The results of the study show that brand image, price, and product quality have a partial and simultaneous effect on consumer purchasing decisions.